The Effect of Thickness and Type of Material on the Sheared Edge Characteristics of Keychain Cranioplasty Plate Blanking Product Using Eccentric Press Machine - Didin Zakariya Lubis; Lea Rachmat Indrasepta; Redyarsa Dharma Bintara; Rizky Ramadhan; Agung Budi Darmawan (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
Keychain cranioplasty plate product has the potential to be produced using the blanking process because it is faster, low-cost, and requires low-energy consumption compared to other mechanical operations. This research aimed to find the effect of material thickness and type on the sheared edge characteristics of keychain cranioplasty plate using the blanking process to meet the international health standard. Experimental research conducted using an eccentric press machine with 40 tons capacity. This research’s test material parameters of titanium (Ti-6AL-4V) and stainless steel (SS-316L) were the 0.5 mm, 0.6 mm, and 0.8 mm thickness with a maximum blanking velocity of 3000 mm/min and 2.5% punch-die clearance. Then, the blanking products were observed using a digital microscope. The results showed that the optimum blanking product quality was found in the titanium (Ti-6AL-4V) and stainless steel (SS-316L) materials with 0.6 mm thickness because it had stable sheared edge characteristics in each zone compared to other variations.